2014
DOI: 10.1186/bf03351706
|View full text |Cite
|
Sign up to set email alerts
|

Closing in on HED meteorite sources

Abstract: Members of the Vesta dynamical family have orbital elements consistent with ejecta from a single large excavating collision from a single hemisphere of Vesta. The portion of Vesta's orbit at which such an event must have occurred is slightly constrained and depends on the hemisphere impacted. There is some evidence for subsequent disruptions of these ejected objects. Spectroscopy suggests that the dynamical family members are associated with material from Vesta's interior that was excavated by the event giving… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2014
2014
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…One of the efforts of the Dawn Science Team has been to investigate the geology of asteroid Vesta through geologic mapping. Geologic mapping attempts to decipher the evolution of a given body (e.g., Coradini et al, 2011;Greeley and Batson, 1990), to provide the context for the spectrally derived composition of the surface (e.g., De Sanctis et al, 2012a), and, in the case of Vesta, to understand the possible link with achondrite meteorites (e.g., McSween et al, 2011;Mayne et al, 2010;Sykes and Vilas, 2001). The first Dawn observations of Vesta's shape and morphology were reported by Jaumann et al (2012).…”
Section: Introductionmentioning
confidence: 99%
“…One of the efforts of the Dawn Science Team has been to investigate the geology of asteroid Vesta through geologic mapping. Geologic mapping attempts to decipher the evolution of a given body (e.g., Coradini et al, 2011;Greeley and Batson, 1990), to provide the context for the spectrally derived composition of the surface (e.g., De Sanctis et al, 2012a), and, in the case of Vesta, to understand the possible link with achondrite meteorites (e.g., McSween et al, 2011;Mayne et al, 2010;Sykes and Vilas, 2001). The first Dawn observations of Vesta's shape and morphology were reported by Jaumann et al (2012).…”
Section: Introductionmentioning
confidence: 99%
“…Zappalá et al (1995) concluded that Vesta possesses a dynamic family of ~240 small asteroids, which are closely associated with it physically and which may have derived from a large collision with Vesta. This Vesta family may have been ejected from one of these large craters (Sykes and Vilas 2001). In addition, observers have identified 18 Vestoids, which are small (~4-10 km) asteroids with Vesta-like spectra and the orbits of which form a bridge connecting Vesta with the ν 6 resonance and the 3:1 Kirkwood gap (Binzel and Xu 1993).…”
Section: Impact-produced Agesmentioning
confidence: 99%
“…Gravitational perturbations by Jupiter from the ν 6 resonance and the 3:1 Kirkwood gap are thought to be "gates" through which objects pass on their way to Earth (Wisdom 1985;Binzel and Xu 1993;Wetherill 1985). Thus, eucrites in our collections likely derived originally from one or more large impacts on Vesta (or a similar body now disrupted) and were brought to Earth by further collisions on one of these smaller, secondary asteroids (Sykes and Vilas 2001).…”
Section: Impact-produced Agesmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent measurements of four Vesta and vestoids reflectance spectra showed an absorption feature near 505 nm corresponding to Fe 2+ in six-fold coordination that is attributed to Ca in pyroxene [6,7]. This absorption feature is also seen in the spectra of eucrite and howardite but not in glassy diogenite [8]. Thus although pyroxene is the main mineral constituent of all three classes (howardite, eucrite and diogenite) of meteorites, there are minor differences in the finer structure of pyroxene in these.…”
mentioning
confidence: 90%